Numerical Analysis of Laser Pattern Effects to Residual Stress on Metal 3D Printing - Jung, Chang Ho; Lee, Moon Gu; Nam, Chanhyuk; Jeon, Yongho (Applied Sciences (Switzerland), 2022)
In this study, a metal 3D printing process was simulated using finite elements methods (FEM), and the specimens were printed under the same conditions. Subsequently, residual stress was measured to validate the results. The thermal-structure two-way coupled analysis confirmed the phenomenon that occurred during the additive process, thereby allowing the residual stress to be calculated more realistically. In addition, to simulate the printing process, a subroutine was con-figured to account for the laser heat input path and layer. The process of stacking and hatching in a snake pattern for an area measuring 5 mm × 5 mm was simulated. Four cases with different rotation angles of the layer pattern were calculated using FEM. The specimens were printed compared with the analysis results. To verify the printed condition of the specimen, computed tomography was performed to confirm the appearance of pores and cracks in the specimen. Cracks appeared in the 180° specimen, and the cause was analyzed based on the analysis results. Subsequently, the residual stress was measured by an X-ray diffractometer and compared; it was confirmed that the average error of the specimen without cracks is 8.86%, which is similar to the analysis results. These results confirm that the FEM model conducted in this study can be used to analyze residual stress and cracks in a material, which are difficult to analyze in previous studies. The FEM model constructed in this study is expected to facilitate investigations into 3D printing phenomena as well as enable a more efficient process design.
Keywords: finite element method; metal 3D printing; residual stress; structure-thermal coupled analysis